MESENTERIC VENOUS THROMBOSIS LEADING TO SMALL BOWEL NECROSIS IN A VIETNAMESE PATIENT WITH PROTEIN C DEFICIENCY: A CASE REPORT (Vietnam Journal of Community Medicine, 2026)
Mesenteric venous thrombosis (MVT) is a rare but life-threatening cause of acute abdominalpain, particularly when associated with congenital protein C deficiency. We present a 65-year-oldVietnamese man with acute epigastric and periumbilical pain and loose stools. Though initiallyhemodynamically stable, he showed signs of peritonitis. Laboratory findings revealedleukocytosis and elevated D-dimer. Contrast-enhanced CT confirmed complete thrombosis of thesuperior mesenteric vein, partial portal vein thrombosis, and bowel wall edema. Protein Cactivity was reduced to 50%. The patient underwent emergency laparotomy with resection of onemeter of necrotic bowel and creation of a double-barrel ileostomy. He received postoperativeanticoagulation with enoxaparin, later switched to apixaban. Discharged in stable condition onpostoperative day 14, he showed resolution of portal vein thrombosis at one-month follow-up.This case underscores the importance of early imaging, recognition of inherited thrombophilia,and timely surgical and anticoagulant therapy in managing MVT.